A Gradation of “Osong” Regional Poetry Reading Skills for Students of SMP Negeri 1 Bulupoddo, Sinjai Regency - Firman - Saleh; Hardianti Hasyim; Burhan Kadir; Sulfiani Sulfiani (La Ogi : English Language Journal, 2022)
This study aims to raise osong as an object in this study because osong is one of the Bugis regional literary works that have a high value. From the results of the blank reading proficiency test, only 3 samples or 15% were able to score 75 and above, while 17 samples or 85% scored below 75. So based on the results of data analysis and discussion of research results, it can be concluded that there is degradation VIII grade students of SMPN 1 Bulupoddo, Sinjai Regency who are not able to read blanks because the number of samples who scored 75 and above did not reach the predetermined criterion level of 85%. Through this study, it is hoped that it can provide an insight into the meaning in literary works, especially those contained in osong. Osong is the result of regional literature and is a reflection of various behaviors or actions, as well as the mindset of the people who gave birth to it (Bugis). Its presence in the community requires serious attention, in line with the current developments. It has become a reality that today's Bugis society is less familiar with osong even more so to understand further the meaning of the work.